Charles Wellington Reed papers - Reed, Charles Wellington, 1841-1926.
Correspondence, diary (1864), ink and pencil sketches, watercolors, prints, lithographs, books illustrated by Reed, citations, military papers, printed material, maps, medals, photographs, and memorabilia relating to Reed's service in the 9th Massachusetts Light Artillery Battery and to military life during the Civil War. Includes two volumes containing circa 700 wartime sketches, some drawn during actual combat.
Library of Congress Prints and Photographs Division.
Artist and soldier.
Collection material in English.
Finding aid available in the available in the Library of Congress Manuscript Reading Room and at
Keywords: United States. -- Army -- Military life; United States. -- Army. -- Massachusetts Artillery Battery, 9th (1862-1865); Art; Illustration of books; Soldiers as artists; United States -- History -- Civil War, 1861-1865 -- Art and the war; United States -- History -- Civil War, 1861-1865 -- Personal narratives; Artists; Soldiers